Therapeutic potential of LINS01 histamine H3 receptor antagonists as antineoplastic agents for triple negative breast cancer - Ospital, Ignacio A. (2024)
Fil: Ospital, Ignacio A. Pontificia Universidad Católica Argentina. Facultad de Ciencias Médicas. Instituto de Investigaciones Biomédicas. Laboratorio de Biología Tumoral e Inflamación; Argentina